Post-traumatic stress disorder and prolonged grief disorder among adolescents after the cianjur earthquake: prevalence and mental health implications - Sugara, Gian Sugiana; Muhajirin, Muhammad; Rahimsyah, Anandha Putri; Irawan, Eris; Fadlillah, Ghania Nurbayani; Aprilya, Tasya; Pratama, Galuh Adji; Haq, Ihsan Nurul (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The Cianjur earthquake on November 21, 2022, caused severe psychological impacts, particularly among adolescents who experienced significant loss or direct exposure to the disaster. This study aimed to analyze the prevalence of Post-Traumatic Stress Disorder (PTSD) and Prolonged Grief Disorder (PGD), and to examine their respective effects on the mental health of adolescent disaster survivors. The research employed a descriptive and correlational quantitative design using a survey approach. A total of 551 adolescents aged 13–17 were selected through purposive sampling based on their exposure to the disaster’s impact. Three instruments were used to collect data: the PTSD Checklist for DSM-5 (PCL-5) to assess post-disaster trauma symptoms; the PGD-13-R to measure prolonged grief severity; and the Mental Health Continuum-Short Form (MHC-SF) to evaluate emotional, psychological, and social well-being. Data were analyzed using descriptive statistics, t-tests, ANOVA, Pearson correlations, and multiple linear regression. Results showed that 18.5% of respondents met the criteria for PTSD and 6.9% for PGD. Regression analysis indicated that PTSD had a significant negative impact on mental health (β = –0.250; p < 0.001), while PGD was not a significant predictor (β = 0.046; p = 0.312). These findings suggest that post-disaster trauma contributes more substantially to mental health deterioration than prolonged grief. Therefore, evidence-based interventions such as Ego State Therapy are recommended to address PTSD symptoms effectively among adolescents affected by the earthquake.